CARDIAC-STAR: prevalence of cardiovascular comorbidities in patients with HR + /HER2 − metastatic breast cancer - Susan Dent; Avirup Guha; Heather Moore; Doris Makari; Rachael McCaleb; Irene Arias; Stella Stergiopoulos; Benjamin Li; Michael Fradley (Cardio-Oncology)
Abstract Background Cardiovascular (CV) comorbidities and concurrent medications with risk of heart rate-corrected QT interval (QTc) prolongation can impact treatment decisions and safety discussions for patients with breast cancer. However, limited data are available regarding their prevalence in patients with HR + /HER2– metastatic breast cancer (mBC). We evaluated the prevalence of CV comorbidities, the use of concurrent medications with risk of QTc prolongation, and treatment patterns in patients with newly diagnosed HR + /HER2 − mBC. Methods This retrospective analysis utilized claims data from Merative™ Marketscan® Commercial and Medicare databases. Claims-based algorithms identified patients with newly diagnosed HR + /HER2– mBC between January 2016 and December 2022. The index date was defined as the first date of an mBC claim during this period. For each patient, data on pre-existing CV comorbidities and first-line treatments were captured for 12 months before and 6 months after the index date, respectively. Results A total of 6525 patients with newly diagnosed HR + /HER2 − mBC were identified. At mBC diagnosis, 61.7% of patients had ≥ 1 CV comorbidity. Of patients with CV comorbidities, 22.5% and 30.6% took 1 or ≥ 2 medications, respectively, with risk of QTc prolongation. First-line use of cyclin-dependent kinase 4/6 (CDK4/6) inhibitors increased from 22.1% of patients with CV comorbidities diagnosed in 2016–2017 to 31.5% of those diagnosed in 2018–2022. Conclusions We found that CV comorbidities and use of medications with risk of QTc prolongation were common in patients with newly diagnosed HR + /HER2 − mBC. These factors should inform treatment decision-making (including CDK4/6 inhibitor selection), safety discussions with patients, and CV monitoring. Graphical Abstract